Philip dos civilizados: the wild boy from stone jungle - Cláudia Rodrigues de Freitas (Universidade Federal de Santa Maria (UFSM), 2014)
This article analyzes the ways of organizing life and the learning processes of a boy experiencing psychic distress and social abandonment from the moment he receives care at a school facility. The experience involves the organization of a network of conversations among those who live with Philip, a boy who was referred to the Special Education Services (SES) based on the autism diagnosis, one of the disorders in the category of Pervasive Developmental Disorders (PDD). The assistance center proposed was aimed at expanding the way of living and learning of Philip. The interventions come up and develop themselves from the invention of playing and become visible through eye contact, smiles, when handling objects that are part of everyday life and mainly by interacting with people around him. The insertion and invention of/in the educational space is aimed at transforming the suffering in life and learning possibilities. The result of this work creates structural transformations in the coexistence between Philip and all the individuals that interact with him. When consolidated conversation networks enable the construction of knowledge areas that are able to support another way of living.